(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status, vitamin D deficiency, and associated factors among adults attending the National Institute of Nutrition in 2025. Methods: A cross-sectional descriptive study was conducted on 245 adults at the National Institute of Nutrition in 2025. Nutritional status was evaluated using anthropometric methods. Vitamin D deficiency was assessed by measuring serum vitamin D3 concentrations collected during the clinical examination. A structured questionnaire was used to evaluate related factors. Results: The results showed that 42.9% of adults had a normal nutritional status, 29.4% were underweight (chronic energy deficiency), and 27.7% were overweight or obese (10.6% overweight, 17.1% obese). The prevalence of central obesity was 40.7%. The rate of serum vitamin D3 deficiency was notably high at 70.2%. Factors significantly associated with vitamin D3 deficiency included female gender and younger age. Specifically, females had a 3.32 times higher risk of vitamin D deficiency than males (OR = 3.321; 95% CI: 1.604-6.876; p = 0.001). Adults in the 20-29 age group had an 83.1% higher risk of deficiency compared to the 40-49 age group (OR = 0.169; 95% CI: 0.062-0.456; p < 0.001) and a 90.9% higher risk compared to the 50-59 age group (OR = 0.091; p < 0.001). Conclusion: The study highlights a double burden of malnutrition among subjects seeking nutritional counseling, with the prevalence of chronic energy deficiency being nearly equal to that of overweight and obesity. The prevalence of vitamin D3 deficiency is at an alarming level. Factors associated with vitamin D deficiency in these adults are particularly prominent among young females working in office environments characterized by sedentary lifestyles and limited sun exposure.